BMP15 mutations associated with primary ovarian insufficiency reduce expression, activity, or synergy with gdf9 (2017)
Context: Bone morphogenetic protein (BMP)15 is an oocyte-specific growth factor, which, together with growth differentiation factor (GDF) 9, regulates folliculogenesis and ovulation rate. Multiple mutations in BMP15 have been identified in women with primary ovarian insufficiency (POI), supporting a pathogenic role; however, the underlying biological mechanism of many of these mutants remains unresolved. Objectives: To determine how mutations associated with ovarian dysfunction alter the biological activity of human BMP15. Design: The effects of 10 mutations in BMP15 on protein production, activation of granulosa cells, and synergy with GDF9 were assessed. Results: Sequencing of 35 patients with POI identified both an unrecognized BMP15 variant (c.986G.A, R329H) and a variant (c.581T.C, F194S) previously associated with the condition. Assessing expression and activity of these and 8 other BMP15 mutants identified: (1) multiple variants, including L148P, F194S, and Y235C, with reduced mature protein production; (2) three variants (R138H, A180T, and R329H) with ;fourfold lower activity than wild-type BMP15; and (3) 3 variants (R68W, F194S, and N196K) with a significantly reduced ability to synergize with GDF9. Conclusions: Mutations in BMP15 associated with POI reduce mature protein production, activity, or synergy with GDF9. The latter effect is perhaps most interesting given that interactions with GDF9 most likelyunderlie the physiologyofBMP15in thehumanovary. Copyright © 2017 by the Endocrine Society.